Enfoques y metodologías de las ciencias sociales : una perspectiva pluralista - Della Porta, Donatella, 1956-; Keating, Michael, 1950-; Vázquez Ramil, Raquel (Akal universitaria. Serie Ciencia política, 2013)
This volume will empower students to choose their own approach to research in the social sciences, to justify this approach, & to situate it within the discipline. It addresses questions of ontology, epistemology & philosophy of social science, as well as issues of methodology & research design essential for a good research proposal.